Mediating effect of job burnout on occupational stress and subjective well-being among research and development enterprise employees in Minhang of Shanghai - Yixuan SUN; Minqi WEI; Qiuwen ZHAO; Jinfeng YANG; Junming DAI (环境与职业医学, 2024)
BackgroundUnder the backdrop of the national innovation-driven development strategy, the increasing occupational stress and job burnout among employees are noteworthy for their impact on employees' subjective well-being. ObjectiveTo clarify the status, distribution characteristics, and the relationship between subjective well-being, occupational stress, and job burnout of employees in research and development (R&D) enterprises, in order to improve their subjective well-being. MethodsA total of 3366 employees from R&D departments at 7 enterprises in Minhang District of Shanghai were selected. The well-being level of the research subjects was investigated by using the World Health Organization Well-Being Index (WHO-5) that yielded total scores from 0 to 25, and a higher total score indicated a higher well-being level; the levels of occupational stress and job burnout were investigated by using the Chinese version of the Job Content Questionnaire, and the Chinese version of the Maslach Burnout Inventory-General Survey (MBI-GS). The scores of WHO-5, JDC, and MBI-GS were incorporated into structural equation modeling (SEM) as numerical variables to analyze their relationship. ResultsThe scores of subjective well-being, occupational stress, and job burnout of employees in the R&D enterprises were 13.30±6.09, 1.12±0.45, and 2.18±1.12, respectively. The positive rates of occupational stress and job burnout were 44.4% and 70.9% respectively, and the positive rate of severe job burnout was 11.7%. There were statistically significant differences in the score of subjective well-being among the participants by gender, age, educational level, marital status, registered residence, working seniority, and jobs (P<0.05); there were statistically significant differences in the positive rate of occupational stress by gender, educational level, marital status, working seniority, and jobs (P<0.05); there were statistically significant differences in the positive rate of job burnout by gender, age, educational level, marital status, registered residence, working seniority, and jobs (P<0.05). There was a negative correlation between subjective well-being and occupational stress (r=−0.1747, P < 0.01), a negative correlation between subjective well-being and job burnout (r=−0.2987, P < 0.01), and a positive correlation between occupational stress and job burnout (r=0.3342, P < 0.01). A structural equation containing partial mediating effect of job burnout on the relationship between occupational stress and subjective well-being was established, and the partial effect accounting for 52.5% of the total effect. ConclusionThe job burnout among employees in R&D companies partially mediates the impact of occupational stress on subjective well-being. Reducing the level of job burnout will help alleviate occupational stress and thus improve employees' subjective well-being.